MENINGKATKAN KEMAMPUAN KOGNITIF PENGENALAN HURUF MELALUI MEDIA KARTU HURUF PADA KELOMPOK B KB ANGGREK MUARA BADAK TAHUN AJARAN 2015/2016 - Masna Masna (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Widya Gama Mahakam Samarinda, 2018)
To improve students' cognitive, most educational institutions always prioritize IQ intellectual intelligence only when creativity is important. This study aims to determine whether the media card letters can improve the cognitive abilities of children group B play group Anggrek Muara Badak year Teaching 2015/2016 or not. Research subjects in this study were children Anggrek play group A Muara Badak which amounted to sixteen children, consisting of nine boys and seven daughters. This research is a classroom action research. This research was conducted in two cycles, namely cycle one and Cycle two, with each stage, that is planning, implementation, observation, and reflection. Data collection techniques used are observations in the form of teacher and student observation sheets, and documentation, Data analysis methods used descriptive analysis with qualitative approach. Classroom Action Research is conducted collaboratively with peers, researchers here act as teachers and peers acting as observers or observers. From the results of the discussion can be concluded that the cartuhuruf media of cardboard can improve the cognitive abilities of children in group B children in play group Anggrek Muara Badak Year Teaching 2015/2016. Can improve. This can be seen in the percentage increase that occurs the average completeness of the achievement of the letters of children recognition achieving the indicator of Excellent Growth before the action is 0.00% to 40.63% in cycle one and after some improvement in cycle two reached 79.67% or twelve children out of six twelve children have reached the Very Good Growing indicator. (2) The teacher gives positive reinforcement to the child, (3) The teacher or researcher teaches by giving praise orally so that children are motivated and feel appreciated. From this research, it can be concluded that the use of letter card media can improve cognitive ability of group B children playing Anggrek Muara Badak in academic year 2015/2016. For that reason that in improving cognitive abilities of children, teachers are advised to use the letter card media.